Wounded for Us: Disability Theology’s Contribution to Christology - Rempel, Daniel (Journal of disability & religion, 2025)
Disability theology began with Christology. Nancy Eiesland’s The Disabled God: A Liberatory Theology of Disability centers upon a vision of God in a sip-puff wheelchair, one given a particular theological backing through analogy to Christ’s post-resurrection wounds. For Eiesland, as Christ is wounded, Christ is disabled. While references to Eiesland’s text are nearly ubiquitous in writing on disability theology, few have examined the Christological implications of Christ wounded for us and its relevance for Christian doctrine. In this paper, I will pick up on one recent dogmatic engagement with Eiesland’s text, Lisa Powell’s The Disabled God Revisited, in order to reflect and further build upon recent Christological endeavors in disability theology, all in order to demonstrate how disability can contribute to our Christological imagination. It is my claim that sustained engagement with disability offers a deeper understanding of the implications of the Christ who was wounded for us.